Customer’s satisfaction towards online shopping: A case study among university’s students / Khairil Aiman Faris Salim ... [et al.] - Salim, Khairil Aiman Faris; Mohamad Nadzir, Ahmad Nur’Alif; Mohamed Zukri, Shamsunarnie; Mohd Fauzi, Noor Zafarina; Ibrahim, Nur Safwati; Ibrahim, Nurul Bariyah (2021)
Online shopping can be defined as the process a customer takes to purchase a service or product over the internet (Veerraju, 2019). Vadivu (2015) also defined online shopping as a process of consumers directly buy goods, services from sellers interactively in real-time without an intermediary service over the internet. Online shopping is the easy solution for busy life in today’s world. Growth in online shopping was from growth in using of smartphones. The report reveals that 78% ofcustomers shopping through mobile phones (Veerraju, 2019). In the present world, online shopping has become the trendiest phenomenon. Rather than moving from place to place, it is more convenient to sit at one place and shop. It all began back in 1979 when Michael Aldrich ‘invented’ online shopping by using videotext, a two-way message service. In 1994, the first online shopping system was introduced by the German company Inter shop. Over the past years, online shopping usage has grown rapidly and grown enormously for delivering, trading information, service, and goods in the current business scenario (Kumar & Mohan, 2018). Nowadays in the twenty-first century, online shopping has increased significantly throughout the world. Globally, e-commerce constituted about a 2.29 trillion-dollar market and is expected to reach 4 trillion dollars by 2020 (Rahman et al., 2018).